Initial Reports of the Deep Sea Drilling Project 1980
DOI: 10.2973/dsdp.proc.515253.165.1980
|View full text |Cite
|
Sign up to set email alerts
|

Water Content and Atterberg Limits of Sediments at Deep Sea Drilling Project Holes 417A and 418A, Legs 51 and 52, West Atlantic Ocean

Abstract: Fourteen water contents and eight Atterberg limits from Hole 417A and two water contents from Hole 418A are reported. The Hole 417A sediments are middle Eocene pelagic clay and radiolarian clay and ooze, which are classified as type CH inorganic clays of high plasticity. Water contents range from 49 to 70 per cent dry weight, liquid limits from 115 to 149 per cent, plastic limits from 34 to 42 per cent, and liquidity indexes from 6 to 39. Values are similar to previous DSDP Atterberg limit data reported in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Davie, Fenske, and Serocki (1978) show the variation in plasticity for different sediment types, including calcareous and siliceous oozes, clay, and volcanic ash from 89 continental margin locations. And Richards and Fager (1980) present data on the plasticity of pelagic clays and radiolarian clay and ooze from the Hatteras Abyssal Plain. Skempton (1953) found that the relationship between the plasticity index and the clay fraction (% less than 2 µm) of any particular combination of clay minerals remained essentially constant.…”
Section: Plasticity Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Davie, Fenske, and Serocki (1978) show the variation in plasticity for different sediment types, including calcareous and siliceous oozes, clay, and volcanic ash from 89 continental margin locations. And Richards and Fager (1980) present data on the plasticity of pelagic clays and radiolarian clay and ooze from the Hatteras Abyssal Plain. Skempton (1953) found that the relationship between the plasticity index and the clay fraction (% less than 2 µm) of any particular combination of clay minerals remained essentially constant.…”
Section: Plasticity Characteristicsmentioning
confidence: 97%
“…Siliceous oozes lie far below the A-line and are classified as OH soils, and calcareous oozes lie below the A-line and show low plasticity. Richards and Fager (1980) show that pelagic clays from 5600 meters in the Nares Abyssal Plain lie above the A-line and are classified as CH soils. On the other hand, Keller, Lambert, and Bennett (1979) find OH sediments covering a broad area of the lower continental slope of the east coast of the United States from the Wilmington Canyon south to Cape Hatteras.…”
Section: Implications Of Plasticity For Sediment Transportmentioning
confidence: 97%
“…Richards and Fager (1980) made measurements onshore of engineering properties on sediments from the upper 140 m of Hole 417A. At Site 418, Donnelly et al (1980) concluded that the only significant variations in physical properties were an increase in velocity and shear strength near 190 m depth and an impedance change coincident with chert layers at 235 m depth.…”
Section: Micropaleontologvmentioning
confidence: 99%
“…Logging confirmed only the feature at 310 m (Salisbury et al , 1980a; see logging section below). Richards and Fager (1980) made measurements onshore of engineering properties on sediments from the upper 140m of Hole 417 A. At Site 418, Donnelly et al (1980) concluded that the only significant variations in physical properties were an increase in velocity and shear strength near 190 m depth and an impedance change coincident with chert layers at 235 m depth.…”
Section: Micropaleontologymentioning
confidence: 99%